Pengaruh Spiritual Marketing, Sharia Compliance, Customer Experience Dan Digitalisasi Banking Terhadap Loyalitas Nasabah Bank Syariah Indonesia - Hasanah, Nur; Rizal, Mohammad; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The rapid development of the Islamic banking industry in Indonesia presents challenges and opportunities for Islamic banks, including Bank Syariah Indonesia (BSI), in increasing customer loyalty. In this context, spiritual marketing, sharia compliance, customer experience, and banking digitalization are the main factors that can influence customer loyalty. This study aims to analyze the influence of these four variables on BSI customer loyalty. A quantitative approach was used with purposive sampling and accidental sampling techniques. The number of samples was determined using the Slovin formula, resulting in 100 respondents. Data was collected through distributing questionnaires to BSI customers and analyzed using SPSS. The analysis methods applied include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis, F test, t test, and coefficient of determination (R²) test. The results showed that spiritual marketing, sharia compliance, customer experience, and banking digitalization significantly affect customer loyalty. These findings confirm that a spiritual value-based marketing approach, compliance with sharia principles, good customer experience, and optimization of banking digitalization play an important role in increasing BSI customer loyalty.This research provides valuable insights for BSI management in designing more effective marketing and service strategies. By improving the quality of spiritual marketing, strengthening compliance with sharia principles, optimizing customer experience, and utilizing digital technology, it is hoped that customer loyalty can continue to be improved. In addition, this study recommends further studies to explore additional factors that can influence customer loyalty, such as service quality and product innovation in Islamic banking Keywords : Spiritual Marketing, Sharia Compliance, Customer Experience, Banking Digitalization, Customer Loyalty, Bank Syariah Indonesia (BSI).